DEVELOPMENT OF GROWING MEDIA FROM SUGAR INDUSTRIAL WASTE - Asadathorn, Pusit; Setthapun, Worajit; Rakwichian, Wattanapong; Kusolsatit, Thassanupan (Journal of Applied Research on Science and Technology (JARST), 2016)
The main waste from sugar production in Thailand were filter cake, and bagasse ash. These wastes were still increased and generally managed by dumping in landfill. The utilization of these wastes was applied to improve of soil properties as soil conditioner. This research aimed to develop of growing media from sugar industrial waste for sustainable waste management. The scopes of study were to analyze chemical properties of sugar industrial waste for identification of hazardous properties following Thailand’s regulation, to determine the optimal mixing condition and size of diameter of developed growing media from sugar industrial waste by stability, bulk density, total porosity, air-filled porosity, water containing capacity, and to explore the optimal mixing condition of developed growing media from sugar industrial waste by the growth condition of Chinese Cabbage (Brassica rapa L.). The results revealed the chemical properties of filter cake, and bagasse ash as non-hazardous waste. These wastes were safe for cultivation utilization. There was no significant difference in bulk density between a mixing ratio and diameter size of growing media, 0.22- 0.33 g/cm3. However, there was correlation between other parameters (total porosity, air-filled porosity, and water containing capacity) and the mixing ratio and diameter size of growing media. Finally, the growth of Chinese cabbage in developed growing media form sugar industrial waste were found the optimal ratio at 4:1 at 4 mm. In conclusion, the utilization of filter cake and bagasse ash in development of growing media can influenced on stability, total porosity, air-filled porosity, and water containing capacity. This research was shown the alternative waste management for Thailand’s sugar industry.